2017
DOI: 10.1002/joc.5030
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric driving mechanisms of flash floods in Portugal

Abstract: The present study aims to investigate how large‐scale atmospheric circulation may influence flash floods in Portugal. For this purpose, weather types (WTs) in a northeastern North Atlantic sector are used and flash floods between 1950 and 2003 were identified in six hydrographic basins: three in the north of Portugal and another three in the south of Portugal. An adapted methodology for flash flood detection on daily discharges is applied. A total of 131 flash floods were detected: 35 in the northern basins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…In addition to extreme precipitation, there are other very important conditioning factors for landslides and floods, such as: physiographic conditions of the basins, soil types, relief, slope or lithological units, in mainland Portugal (e.g. Henriques, Santos, Santos, & Fragoso, 2017;Santos & Reis, 2017;Zêzere et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to extreme precipitation, there are other very important conditioning factors for landslides and floods, such as: physiographic conditions of the basins, soil types, relief, slope or lithological units, in mainland Portugal (e.g. Henriques, Santos, Santos, & Fragoso, 2017;Santos & Reis, 2017;Zêzere et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The synoptic‐scale atmospheric processes leading up to intense rainfall and flash flooding events have been investigated in a number of countries. Santos et al () used weather types to investigate flash flooding across three river basins in Portugal, although the study was not limited to the summer, while Barbero et al () found that disturbances associated with the jet stream and cutoff upper‐level lows were related to the occurrence of 1‐hr annual maximum precipitation across much of the United States. Summer flash flood studies in the United Kingdom have generally focused either on individual case studies or convective‐scale processes (e.g., Flack et al, ; Golding et al, ; Warren et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well known that extreme precipitation events in Portugal occurring during the extended winter months (October-March) are often associated with landslides and flooding in the major river basins [1][2][3] and, with flash floods in small watersheds or urban areas [4,5] which can produce socio-economic impacts. Thus, in order to prevent and manage the associated effects and risks, there is a clear need for better characterization of the associated extreme meteorological metrics and the nature of likely unusual strong atmospheric driving mechanisms.…”
Section: Introductionmentioning
confidence: 99%